2023
DOI: 10.3390/foods12142734
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages for the Targeted Control of Foodborne Pathogens

Abstract: Foodborne illness is exacerbated by novel and emerging pathotypes, persistent contamination, antimicrobial resistance, an ever-changing environment, and the complexity of food production systems. Sporadic and outbreak events of common foodborne pathogens like Shiga toxigenic E. coli (STEC), Salmonella, Campylobacter, and Listeria monocytogenes are increasingly identified. Methods of controlling human infections linked with food products are essential to improve food safety and public health and to avoid econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 168 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…Existing studies have found that cockroaches can carry about 50 species of pathogenic bacteria, of which STEC, Campylobacter and Salmonella species are often thought to be linked to outbreaks of foodborne illness 50 . A meta-analysis found that cockroaches caught in the food establishment were contaminated by E. coli , Klebsiella pneumoniae and Salmonella spp., and that human infection with these bacteria might be transmitted through cockroaches 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have found that cockroaches can carry about 50 species of pathogenic bacteria, of which STEC, Campylobacter and Salmonella species are often thought to be linked to outbreaks of foodborne illness 50 . A meta-analysis found that cockroaches caught in the food establishment were contaminated by E. coli , Klebsiella pneumoniae and Salmonella spp., and that human infection with these bacteria might be transmitted through cockroaches 51 .…”
Section: Discussionmentioning
confidence: 99%
“…E. coli O157, a microorganism that lives in the intestines of live animals and is excreted through their faeces, potentially contaminating food, water and the environment, was isolated from cockroaches 52 , 53 . The STEC strain can survive harsh food processing conditions and has been a hot spot for persistent cross-contamination incidents in food processing environments 50 . Aeromonas species are found in aquatic environments, food, vertebrates and invertebrates, ticks and insects, of which Aeromonas hydrophila is believed to be pathogenic and clinically significant to humans 54 .…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that reducing contamination without the complete elimination of contaminant bacteria can be an efficacious method of assuring food safety regardless since bacterial load is important in disease evolution. However, a phage cocktail against a target pathogen may not be suitable in different niches such as animal-, plant-, or food-processing environments, so the "niche-specific" use of phages in the food processing system was recently proposed for the effective control of pathogens [46]. More field-scale studies are required to affirm the efficacy of phages in more real-world food production systems.…”
Section: Bacteriophages and Relative Resistancementioning
confidence: 99%
“…STEC biofilms have been associated with an increased tolerance to common sanitizers such as chlorine and quaternary ammonium compounds, probably due to a combination of bacterial resistance mechanisms [ 17 , 18 ]. Several decontamination strategies, including the use of chemical disinfectants (such as sodium dichloroisocyanurate, quaternary ammonium compounds, chlorine, peracetic acid, and lactic acid), heat treatment (pasteurization), washing (water), and chilling, are commonly used during food processing to reduce the risk of pathogens entering the food chain [ 11 , 19 ]. However, these strategies are not completely effective.…”
Section: Introductionmentioning
confidence: 99%